Classification of Iberian pigs as to their nutrition through the ChemSensor technique - Carrasco J.A.; Giménez L.; Duque J.P. (7th International Symposium on the Mediterranean Pig, 2012)
We have developed a classification method to discriminate the quality of Iberian pigs with different feeding patterns (bellota, recebo, extensive and intensive feeding) in view of the large price differences encountered in the market depending on availability of acorns diet or other type of food. We used the ChemSensor Technique which combines a gas chromatograph with a mass detector as well as a liquid autosampler and a headspace system. Our starting material consisted of 207 samples of back side bacon extracted from pigs previously fattened with different feeding systems and subsequently fatty acid and volatile compound analysis were performed. Up to 75% of the samples were analyzed in a first step obtaining a prediction model that applies to the remaining 25% of samples. A proper software adds mass abundances in the range of m/z scanned (41-550) for further analysis by a chemometric software (Pirouette, by Infometrix Inc.). The classification method used was established with SIMCA (Soft Independent Modelling Class Analogy). Our results indicate a satisfactory classification up to 96% and a prediction of ca. 90% in bellota-type pigs and in intensive type and somewhat lower in recebo and extensive types.
7. International Symposium on the Mediterranean Pig, 2010/10/14-16, Córdoba (Spain)